Implementasi Artificial Intelligence dalam Manajemen Operasional Perbankan: Implikasi terhadap Efisiensi, Manajemen Risiko, dan Kepuasan Nasabah - puspita, Gina (Fakultas Ekonomi Universitas Gresik, 2024)
The development of digital technology has driven significant transformation in the banking sector, particularly through the implementation of Artificial Intelligence (AI), which is believed to improve efficiency, strengthen risk management, and enhance customer satisfaction. However, previous research tends to focus on a single aspect, leaving the interrelationships between dimensions unclear, particularly in the context of a developing country like Indonesia. This study aims to simultaneously analyze the impact of AI implementation on operational efficiency, risk management, and customer satisfaction. The research method used is a quantitative explanatory approach with a sample of customers and bank managers who have used AI-based services. Data were collected through a questionnaire with a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that AI significantly impacts operational efficiency, risk management, and customer satisfaction, with efficiency proving to be an important mediator between AI implementation and customer satisfaction. These findings confirm that the success of AI depends not only on technical capabilities but also on governance, digital literacy, and a combination of high-tech and high-touch strategies. The implications of this research emphasize the need for banks to integrate AI in an ethical, transparent, and customer-oriented manner, while also encouraging regulators to provide an adaptive policy framework to strengthen public trust in digital banking services.